(untitled) (Journal of Laboratory Animal Science, 2022)
Polymicrobial infections tend to be more complex and results in aggressive forms of diseases that often exhibit multi drug resistance and impact the therapeutic measures. Despite the severity of such infections, polymicrobial etiology represents a neglected concept in making a clinical diagnosis. In present report, we describe a case of ocular infection associated with Staphylococcus aureus and Candida albicans in a female BALB/c mouse. This report not only underscores the importance of polymicrobial infection but also highlights the occupational risk of methicillin-resistant Staphylococcus aureus to research and animal care personnel’s in animal research facility